Severe megaloblastic anaemia in an infant - Rodrigues, V (2011)
Vitamin B(12) or cobalamin deficiency, a rare clinical entity in pediatric age, is found most exclusively in breastfed infants, whose mothers are strictly vegetarian non-supplemented or with pernicious anaemia. In this article, the authors describe a 10-month-old infant admitted for vomiting, refusal to eat and prostration. The infant was exclusively breastfed and difficulties in introduction of new foods were reported. Failure to thrive since 5 months of age was also noticed. Laboratory evaluation revealed severe normocytic normochromic anaemia and cobalamin deficit. A diagnosis of α-thalassemia trait was also made. Maternal investigation showed autoimmune pernicious anaemia. This case shows the severity of vitamin B(12) deficiency and the importance of adopting adequate and precocious measures in order to prevent potentially irreversible neurologic damage.